Āpiti hono, tātai hono: A collaborative bicultural social work research approach - Mooney H; Deverick K (Aotearoa New Zealand Association of Social Workers)
INTRODUCTION: This article introduces the qualitative research design of a research report completed in 2019 that focused on collaborative bicultural social work practice in Aotearoa New Zealand. A major focus of this article is the relationship between the Pākehā researcher (and tauira) and the Māori social work research supervisor. Therefore, reflective accounts are provided throughout the article where we have emphasised the value of the supervision process and bicultural collaborative relationship. METHODS: The research utilised social constructivist theory and a decolonising, Te Tiriti o Waitangi lens. Data were collected from semi-structured interviews with four registered social workers. An integrated narrative approach to analysis allowed for multiple narrative levels to be considered. The researcher and supervisor modelled a collaborative bicultural relationship in the research design process. FINDINGS: The article presents the process of research design and a critical reflection on the challenges and benefits of a collaborative bicultural supervision relationship. We argue that an interrogation of the cultural positioning of the researcher and supervisor is essential in research design in Aotearoa New Zealand. These were also reflected in the findings reported in a separate article in this issue (Deverick & Mooney, 2023). IMPLICATIONS FOR PRACTICE, RESEARCH OR POLICY: Reflections of bicultural research will be of interest, particularly to other Pākehā, Tauiwi tauira interested in exploring how they can contribute to the bicultural discourse in research. Research supervisors may also be interested.
Keywords: 1607 Social Work